Calcium Pyrophosphate Deposition Disease of the Temporomandibular Joint - Srinivasan, Vasisht; Wensel, Andrew; Dutcher, Paul; Newlands, Shawn; Johnson, Mahlon; Vates, George Edward (Journal of Neurological Surgery Reports, 2012)
Calcium pyrophosphate dihydrate deposition disease (CPDD, tophaceous pseudogout) is a rare crystal arthropathy characterized by calcium pyrophosphate crystal deposition in joint spaces, episodes of synovitis, and radiological features of chondrocalcinosis. We present a case of 61-year-old woman who presented with left temporomandibular joint (TMJ) pain, difficulty chewing, left facial numbness, left-sided hearing loss, and left TMJ swelling. Imaging of the temporal fossa revealed a large mass emanating from the temporal bone at the TMJ, extending into the greater wing of the sphenoid and involving the mastoid bone and air cells posteriorly. Fine needle aspiration demonstrated polarizable crystals with giant cells. Intraoperatively, the TMJ was completely eroded by the mass. Final pathology was consistent with tophaceous pseudogout. CPDD has rarely been reported involving the skull base. None of the cases originally described by McCarty had TMJ pseudogout. Symptoms are generally pain, swelling, and hearing loss. Management is nearly always surgical with many patients achieving symptomatic relief with resection. CPDD is associated with many medical problems (including renal failure, gout, and hyperparathyroidism), but our patient had none of these risk factors. This case demonstrates that CPDD can involve the skull base and is best treated with skull base surgical techniques.
Keywords: temporomandibular joint; calcium pyrophosphate; CPDD; chondrocalcinosis; tophaceous pseudogout